Cost‐Effectiveness of Monitoring Patients Post‐Stroke With Mobile ECG During the Hospital Stay - Lan Gao (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background The effectiveness of a nurse‐led in‐hospital monitoring protocol with mobile ECG (iECG) was investigated for detecting atrial fibrillation in patients post‐ischemic stroke or post‐transient ischemic attack. The study aimed to assess the cost‐effectiveness of using iECG during the initial hospital stay compared with standard 24‐hour Holter monitoring. Methods and Results A Markov microsimulation model was constructed to simulate the lifetime health outcomes and costs. The rate of atrial fibrillation detection in iECG and Holter monitoring during the in‐hospital phase and characteristics of modeled population (ie, age, sex, CHA2DS2‐VASc) were informed by patient‐level data. Costs related to recurrent stroke, stroke management, medications (new oral anticoagulants), and rehabilitation were included. The cost‐effectiveness analysis outcome was calculated as an incremental cost per quality‐adjusted life‐year gained. As results, monitoring patients with iECG post‐stroke during the index hospitalization was associated with marginally higher costs (A$31 196) and greater benefits (6.70 quality‐adjusted life‐years) compared with 24‐hour Holter surveillance (A$31 095 and 6.66 quality‐adjusted life‐years) over a 20‐year time horizon, with an incremental cost‐effectiveness ratio of $3013/ quality‐adjusted life‐years. Monitoring patients with iECG also contributed to lower recurrence of stroke and stroke‐related deaths (140 recurrent strokes and 20 deaths avoided per 10 000 patients). The probabilistic sensitivity analyses suggested iECG is highly likely to be a cost‐effective intervention (100% probability). Conclusions A nurse‐led iECG monitoring protocol during the acute hospital stay was found to improve the rate of atrial fibrillation detection and contributed to slightly increased costs and improved health outcomes. Using iECG to monitor patients post‐stroke during initial hospitalization is recommended to complement routine care.